ChemInform Abstract: Probing Secondary Interactions in Biomolecular Recognition by Dynamic Combinatorial Chemistry. Issue 28 (15th July 2014) - Ulrich, Sebastien; Dumy, Pascal
Abstract Review: 207 refs.